Memories of post-imperial nations: the aftermath of decolonization, 1945-2013 - Rothermund, Dietmar (Cambridge University Press, 2015)
"Brings together the varying perspectives with historians attempting to bind memory and its experience of different post-imperial nations -- Britain, Netherlands, France, Belgium, Italy, Portugal and Japan"--Provided by publisher
Literaturangaben
Keywords: Japan -- Colonies -- Historiography; Europe -- Colonies -- Historiography; Aufsatzsammlung; Geschichte 1945-2013; Kollektives Gedächtnis; Geschichtsschreibung; Kolonialmacht; Entkolonialisierung